War crimes the left's campaign to destroy our military and lose the war on terror - Patterson, Robert (Crown Forum, 2007)
Conservative pundit Patterson (USAF, Ret.) lays bare the Left's campaign against their own nation's armed forces, revealing: the roots of liberal enmity toward our military; the five liberal lies about the war on terror; how the mainstream media, Hollywood, and academia perpetuate these myths; how liberal politicians engage in seditious acts for political gain, and what the costs of these acts are; how America can and must defeat the liberal assault on America's ability to defend itself against its enemies. Interviews with hundreds of soldiers, sailors, and airmen--including many on the ground in Iraq--reveal the alarming degree to which their burden is increased by second-guessing, pessimism, and outright revulsion for their mission on the part of the people they are fighting for.--From publisher description.